Mehrsprachigkeit im Spiegel des Buchdrucks: Das spanische Italien im 16. und 17. Jahrhundert - Ambrosch-Baroua, Tina (Modern Academic Publishing, 2016)
During the sixteenth and seventeenth century large parts of Italy were under Spanish dominion, the consequence of which was a linguistic contact that lasted over 200 years. However, due to the traditionally tight link between Italian language historiography and national historiography, the multilingual communicative space of Spanish Italy has only recently become an object of research. By focusing on four Spanish-dominated areas - the two metropolises of Naples (Regno di Napoli) and Milan (Milanesado), as well as the two islands of Sicily (Regno di Sicilia) and Sardinia (Regno di Sardegna) - the present work therefore presents a fundamental, extensive, and comparative case study of the history of plurilingualism and of letterpress printing in Italia spagnola. For the first time, even methodologically, letterpress printing will be considered as an indicator of plurilingualism, and not simply as a gauge for Tuscanisation, as scholars have previously concluded. The corpus, which has been elaborated on the basis of a specifically developed online title-database consisting of over 3.000 Spanish, bi- and multilingual printed works, is analyzed by combining quantification and qualification methods. The statistical evaluation of book production and distribution of languages and domains associated therewith have been integrated, or rather validated, by qualitative comments on exemplary single works. Herein, the following questions have been examined: How is multilingualism generally, and with regard to the Spanish language in particular, reflected in book production? How often and in which domains of discourse is Spanish used? Which profiles of competence of the producers (authors and printers) and the recipients can be qualitatively traced through single printed works? What evidence of the conventionalization of multilingualism in the form of linguistic teaching material can be provided? Which plurilinguistic practices can be reconstructed on the basis of the prints? Is bilingualism or multilingualism reflected on (and eventually how), and, if so, how is it discussed and assessed? How does the respective communicative space, characterized by the constant presence of the Spanish language, configure itself in the consciousness of the communicants within the field of perceptive linguistics? Thus, the aim was to investigate the degree of Hispanicization of Spanish Italy on the basis of the quantified printed language, and to discuss the practices of multilingualism, the attitudes towards the Spanish language, and how plurilingualism was reflected in selected printed works and their paratexts. The overall segment of the Spanish book production can be defined as a marginal phenomenon with a limited target group, and therefore multilingualism in Spanish Italy, when considered through letterpress printing, assumes an elitist status. However, the respective empirical results of the four partial corpora offer prominent regional differences, with each of the four communicative spaces presenting with their own, specific profile of multilingualism. The contrast of the single cases thus leads to a typology between Spanish Sardinia and the other three areas. The case reconstructions furnish the evidence that Spanish Sardinia, for reasons beyond existing language politics, represents the exception, or rather, the extreme case of problem-focused plurilingualism and Hispanicization. The remaining three areas (Naples, Milan and Sicily) bundle to form a second type - on account of their indifference towards language diversity as well as their pragmatic, mostly implicit, conventionalized handling of multilingualism, they can be classified as normal cases of language contact.